A Unified Field Approach On Fractional-Ordered Micropolar Thermoelasticity with Diffusion (Global Journals of Research in Engineering, 2011)
The present paper is completely devoted on derivation of some basic fundamental relations in generalized thermodiffusive micropolar elasticity with fractional-ordered derivatives. The generalized heat conduction and mass diffusion equations have been modified by using fractional calculus. A variational principle is obtained and hence the uniqueness theorem for those equations has been proved.
Keywords: Fractional calculus; Micropolar elasticity; Thermodiffusion; Variational principle; Uniqueness theorem